MULTI CRITERIA SUPPLIER SELECTION USING A HYBRID FUZZY AHP- TAGUCHI TECHNIQUE: THE CASE OF TEXTILE INDUSTRY - Wilson Kosasih; Vieren Yulies Triyani; Ahmad Ahmad; Carla Olyvia Doaly (Jurnal Ilmiah Teknik Industri, 2020)
This paper discusses a method that integrates Fuzzy AHP with Taguchi Loss Function. The method used to select suppliers with various criteria. This various criteria will be considered to get the best supplier. This research was conducted at a textile company in Indonesia for the cotton product 41166. The purpose of this research is to apply techniques to improve the performance of Fuzzy AHP by considering the cost of losses as small as possible. Research data obtained from the survey results using questionnaires and company factual data in the form of costs of losses incurred due to improper quantity of raw materials, quality of raw materials that are not in accordance with standards, delays in delivery, prices that exceed expectations, and poor service or response. The results of this research shown the value of losses incurred by 1st, 2nd, 3rd, 4th suppliers respectively for $ 2.23, $ 671.12, $ 815.57, and $ 1243.64. Among four suppliers, the best supplier with the smallest loss value is first supplier.